Rationalism Values of Junior High School Students Using Digital Media Worksheets Geometry Content Agrotourism Context - Kurniawan, Ahmad Afrideni; Aisyah, Nyimas; Meryansumayeka, Meryansumayeka; Lesmana, Hendra; Maat, Siti Mistima (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2025)
One of the mathematical values is the value of rationalism. This study aims to describe the value of rationalism of junior high school students using digital media worksheets in the context of agrotourism on the surface area of cylinders with research subjects of 3 grade IX students. Data collection was carried out using tests and interviews. The results of this study are that learning using digital technology-based learning media worksheets with geometry content in the context of agrotourism can bring up the value of rationalism. Students can bring up indicators of representing real objects into mathematical objects and writing information that is in accordance with the elements of the cylinder, investigating the appropriate nets in the problem object and writing down the reasons for each step of the solution. The most frequent indicators are representing real objects into mathematical objects, writing down the reasons for each step of the solution and making conclusions. The dominant difficulty is that students make mistakes in drawing conclusions due to errors in investigation activities and understanding mathematical concepts regarding the surface area of spatial shapes.